The Sustainability Status of Boat Lift-Net Fisheries in Kao Bay, North Maluku Province - Gaus, Hardianti; Taeran, Imran; Rumagia, Faizal; Irham, Irham; Achmad, M. Djanib; Muksin, Darmiyati (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2023)
The boat lift-net used by fishermen in Saramaake and Akesahu Village consist of one-boat lift-net and two-boat lift netLocal fishermen always operate boat lift-net fishing gear continuously without knowing the existence of available fish resources and the sustainability status in the waters around Kao Bay. The objectives of this research are to assess the sustainability status of the boat lift-net fisheries operated in the Kao Bay. The data was obtained through survey and indepth interview to the respondent that related to the research objective. Data analysis was carried out. Analysis of the sustainability of the fishing boat fishery was carried out using a multidimensional scaling (MDS) approach called RAP-PL which is a development of the RAPFISH method which is used to assess the sustainability status of capture fisheries. The results of the the multidimensional analysis of the sustainability status of the boat lift-net fihery in Saramaake and Akesahu Village based on existing conditions, in Saramaake Village the index value was obtained at 56.05%, and for Akesahu Village the index value was slightly increased, namely 57.22%